Pengaruh Komunikasi Pemasaran Perusahaan terhadap Kesadaran Merek Pelanggan - Dita Amanah; Dedy Ansari Harahap (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2018)
The purpose of this study is to describe the effect of corporate marketing communications on customer brand awareness. Marketing communications should be done by the company to introduce or notify their products to customers. It can be done when the company introduces new products or products that are already on the market. Marketing communication also called promotion can be done through advertising, sales promotion, personal sales and publications. The method tried to compare the previous study and journals. The findings from previous studies show that marketing communications can shape brand awareness for customers. When a customer knows that a product will be launched or is already in the market, then the customer is aware and finally buys if the product matches their needs or desires. Brand awareness needs to be built in the minds of customers in order to be aware of the existence of the brand so that customers can identify brands into certain product categories.